If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + -7x = 2x + 11 Reorder the terms: -16 + -7x = 11 + 2x Solving -16 + -7x = 11 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -16 + -7x + -2x = 11 + 2x + -2x Combine like terms: -7x + -2x = -9x -16 + -9x = 11 + 2x + -2x Combine like terms: 2x + -2x = 0 -16 + -9x = 11 + 0 -16 + -9x = 11 Add '16' to each side of the equation. -16 + 16 + -9x = 11 + 16 Combine like terms: -16 + 16 = 0 0 + -9x = 11 + 16 -9x = 11 + 16 Combine like terms: 11 + 16 = 27 -9x = 27 Divide each side by '-9'. x = -3 Simplifying x = -3
| v=18(4)(1) | | 4x+8=98-5 | | 8x+13=2x+187 | | x=y-4 | | v=1841 | | x^2+8x+9=-9 | | 180(3.14)=2(3.14)r(10) | | -10-6x=6x-10 | | (9x-1)2=22 | | -16t^2+4t+8=0 | | (X+2)9-(X-8)3=3 | | a=3.14(5)(5) | | 51-7x=20x+18 | | 3(4n-3)=18 | | X+13=15-2x | | 6n-7=41 | | 18(3.14)=2(3.14)r | | 4q+12=-18 | | 25x+10+1.75x=40 | | 7x-y=-7 | | 9=5x-31 | | y+7=6x | | 4x=-58 | | 5b^2+29b+20=0 | | 4m-7=5+m | | 5(x+3)=2x+30 | | 4x-g=58 | | a=1/2(10+18)22 | | d+45=20 | | 0.4x+2.6=2.0 | | x-17=47-3x | | 5x+7=7x+21 |